2012
DOI: 10.2478/v10219-012-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microemulsion on liberation of indomethacin from hydrophilic and lipophilic gel

Abstract: The paper is focused on liberation of indomethacin from gels and the influence of microemulsion´s presence in the system. Liberation of drug was performed in vitro through a semipermeable membrane and drug quantity was determined spectrophotometrically. Our results pointed out that the influence of microemulsion system on drug liberation depends on the gel selection. The presence of o/w microemulsion in the lipophilic gel (aerosil in liquid paraffin) increased the released amount of the drug approximately 50%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The highest percentage of released indomethacin was determined when a mixture of microemulsion gel with higher chitosan content was used. On the basis of our previous study, 29 it can be concluded that this prepared chitosan gel with microemulsion is more suitable for permeation of indomethacin than commercial Indobene Gel R . Chitosan gels could be convenient for the controlled release of drugs.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The highest percentage of released indomethacin was determined when a mixture of microemulsion gel with higher chitosan content was used. On the basis of our previous study, 29 it can be concluded that this prepared chitosan gel with microemulsion is more suitable for permeation of indomethacin than commercial Indobene Gel R . Chitosan gels could be convenient for the controlled release of drugs.…”
Section: Discussionmentioning
confidence: 74%
“…13 The effect of microemulsion on liberation of indomethacin from hydrophilic (carbopol) and lipophilic gel (aerosil in liquid paraffin) was also evaluated. 29 In this study, chitosan hydrogel formulations containing microemulsion as vehicles for indomethacin as drug were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Microemulsions due to their versatile physicochemical attributes like optically clarity, thermodynamic stability and droplet size ranging from 10-140nm stands as delivery of choice for topical dermal application. It can interact with the stratum corneum resulting into the increased permeability due to structural rearrangement lipid layers 1,2 . Skin diseases are result of internal factors like inability of the skin to retain moisture, decrease in Elastin production, less turnover of new skin cells and external factors like lifestyle and environment of the individual like smoking, exposure to sun, exposure to cold, poor diet, too much stress and lack of exercise etc.…”
Section: Introductionmentioning
confidence: 99%